Anomalous back-arc volcanism due to subducting linear topographic features - Ichihara, Mie (2019)
Back-arc volcanism along the Pacific Ring of Fire exhibits different types of volcanoes. Among them, anomalous volcanoes can be spotted either as uncommonly large volcanoes, or as isolated volcanoes in an region with few or no volcanism. These anomalous arc volcanoes are often correlated with the existence of a linear topographic feature (fracture zone, seamounts alignment, ridge) on the subducting seafloor. Based on an accurate volcano volume estimation, as well as a quantification of topographic anomalies on the oceanic side, we challenge this correlation and assess the relevance of a quantitative link between subducting topographic anomalies and uncommon back-arc volcanism.